An in vivo Model for the Assessment of Acute Fibrinolytic Capacity of the Endothelium - Newby, David E; Wright, Robert A; Ludlam, Christopher A; Fox, Keith A A; Boon, Nicholas A; Webb, David J (Thrombosis and Haemostasis, 1997)
The effects on blood flow and plasma fibrinolytic and coagulation parameters of intraarterial substance P, an endothelium dependent vasodilator, and sodium nitroprusside, a control endothelium independent vasodilator, were studied in the human forearm circulation. At subsystemic locally active doses, both substance P (2-8 pmol/min) and sodium nitroprusside (2-8 μg/min) caused dose-dependent vasodilatation (p <0.001 for both) without affecting plasma concentrations of PAI-1, von Willebrand factor antigen or factor VIII:C activity. Substance P caused local increases in t-PA antigen and activity (p <0.001) in the infused arm while sodium nitroprusside did not. At higher doses, substance P increased blood flow and t-PA concentrations in the noninfused arm. We conclude that brief, locally active and subsystemic infusions of intraarterial substance P cause a rapid and substantial local release of t-PA which appear to act via a flow and nitric oxide independent mechanism. This model should provide a useful and selective method of assessing the in vivo capacity of the forearm endothelium to release t-PA acutely.